Pelatihan Kewirausahaan Perempuan Berbasis Potensi Lokal untuk Mengembangkan Kawasan Industri Kecamatan Pakenjeng Kabupaten Garut - Akhmad Khori dan Lilis Irmawatie (LPPM UNINUS, 2012)
Society empowerment especially women's through entrepreneurship education programs based on local potential is one of the strategies in extending women’s entrepreneurship and creating job vacancies so that they earn incomes for improving the welfare of their families and industries. The entrepreneurship education provided red bricks and salty fish making. Women who were involved in entrepreneurship education are housewives and dropped out from Pakenjeng schools area in Garut to the tune of 40 people. Community empowerment model implemented in this program is harmonizing four elements, namely academics, business actors, government and society. This program has successfully trained as many as 40 people so that they could earn better incomes to improve their families’ welfare.